Adaptation of Remarried Couples in Mandailing: Cultural and Traditional Perspectives from Nagari Sungai Aur, West Pasaman Regency - Rahmi, Annisa; Fachrina, Fachrina; Jendrius, Jendrius; Syafiola, M. Fedro (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. Remarriage represents a significant phenomenon affecting family dynamics in contemporary society, particularly given the rising divorce rates. This study aims to examine adaptation strategies employed by remarried couples in Nagari Sungai Aur, West Pasaman District, within the Mandailing cultural context. Using a qualitative methodology through in-depth interviews and observations, the research explores how couples navigate complexities such as role restructuring, effective communication, trust reconstruction, and integrating children from previous marriages. Data were collected through purposive sampling, focusing on remarried couples within the past three years who had children from previous marriages. Data analysis followed Miles and Huberman's three-stage approach: data coding, data presentation, and conclusion drawing. The findings reveal that adaptation occurs through behavioral modifications, maintaining communication, understanding character differences, building relationships with stepchildren, and strengthening ties with the husband's extended family. Challenges encountered include economic issues and feelings of alienation due to the patrilocal system, which emphasizes the husband's extended family as the center of familial ties. This research highlights the importance of adaptive strategies in strengthening household harmony for remarried women within the Mandailing cultural context. Practical implications include guidance on improving communication, fostering positive relationships with stepchildren, and addressing cultural challenges to enhance marital resilience. Keywords: Remarriage, adaptation strategies, mandailing culture, patrilocal system. Abstrak. Pernikahan ulang merupakan fenomena signifikan yang memengaruhi dinamika keluarga di masyarakat kontemporer, terutama dengan meningkatnya angka perceraian. Penelitian ini bertujuan mengkaji strategi adaptasi oleh pasangan yang menikah ulang di Nagari Sungai Aur, Kabupaten Pasaman Barat, dalam konteks budaya Mandailing. Dengan menggunakan metode kualitatif melalui wawancara mendalam dan observasi, penelitian ini mengeksplorasi bagaimana pasangan menghadapi berbagai kompleksitas, seperti restrukturisasi peran, komunikasi yang efektif, rekonstruksi kepercayaan, dan integrasi anak-anak dari pernikahan sebelumnya. Data dikumpulkan melalui purposive sampling, yang berfokus pada pasangan yang menikah ulang dalam tiga tahun terakhir dan memiliki anak dari pernikahan sebelumnya. Analisis data mengikuti pendekatan tiga tahap Miles dan Huberman: pengodean data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa adaptasi dilakukan melalui modifikasi perilaku, menjaga komunikasi, memahami perbedaan karakter, membangun hubungan dengan anak tiri, dan memperkuat ikatan dengan keluarga besar suami. Tantangan yang dihadapi meliputi masalah ekonomi dan perasaan terasing akibat sistem patrilokal, yang menekankan keluarga besar suami sebagai pusat hubungan kekeluargaan. Penelitian ini menyoroti pentingnya strategi adaptasi dalam memperkuat keharmonisan rumah tangga bagi perempuan yang menikah ulang dalam konteks budaya Mandailing. Implikasi praktis mencakup panduan untuk meningkatkan komunikasi, membangun hubungan yang positif dengan anak tiri, dan mengatasi tantangan budaya guna meningkatkan ketahanan dalam pernikahan. Kata Kunci: Pernikahan ulang, strategi adaptasi, budaya mandailing, sistem patrilokal.